Follow the dirt road [videorecording] an introduction to intentional communities in the 1990's - Gauthier, Monique ([S.l.] The Cinema Guild, 1992)
Examines the situation of communes or intentional communities in the U.S. today. Members of over two dozen intentional communities throughout the U.S. belie these media stereotypes of discussing the organizational diversity of communal life, their motivations for choosing this lifestyle and its advantages and challenges.
Narrator, Vicky Mountain.
Keywords: Collective settlements -- United States; Community organization -- United States